Importation and Transmission of Parasitic and Other Infectious Diseases Associated with International Adoptees and Refugees Immigrating into the United States of America. (25th October 2015) - Smith Darr, Jordan; Conn, David Bruce
Abstract : Each year, hundreds of millions of people travel across international borders or even oceans, and up to 230 million may remain for long periods. Among these, 3–5 million settle permanently in their new homes, with about 1 million migrating permanently to the United States of America. This may result in transport of parasites and other pathogens, which might become established, infecting individuals in the new location. Beyond concern of disease spread, the health of migrants is of concern since the rigors, circumstances, and living conditions surrounding migrations may increase the vulnerability of migrants to infections. International adoptees and refugees are a small subset of these migrants but are of special significance inasmuch as adoptees may be more vulnerable to infection due to their immature immune status, and refugees may be more vulnerable due to substandard living conditions. Both originate from diverse regions, but often from environments of low hygiene and health care standards. This review examines recent examples of infections reported from adoptees and refugees entering the USA through 2010, highlighting the most common origin countries and the diseases most frequently involved, including Chagas disease, Balamuthia amebic meningoencephalitis, giardiasis, microsporidiosis, hepatitis, measles, pertussis, tuberculosis, malaria, intestinal helminths, and syphilis.